The Influence of Entrepreneurial Orientation an Innovation Capability by Absorptive and Networking Capability: A Case Study of Tempe Chips SMES in Malang - Reni Rupianti; Ananda Sabil Hussein; Ferry Firdaus (Syntax Corporation Indonesia, 2022)
This study aims to analyze the effect of entrepreneurial orientation, absorptive capability, and networking capability on innovation capability; examine the effect of entrepreneurial orientation on innovation capability mediated by absorptive capability and networking capability. The sample in this study was 89 owners of SME owners of tempeh chips in the Sanan Industrial Center of Malang. Data analysis using Partial Least Squares (PLS). The results show that entrepreneurial orientation has a direct positive effect on innovation capability; entrepreneurial orientation does not affect absorptive capability; entrepreneurial orientation has a direct positive effect on networking capability; absorptive capability has a direct positive relationship to innovation capability; networking capability has a direct positive impact on innovation capability; entrepreneurial orientation does not affect innovation capability through absorptive capability; entrepreneurial orientation has a positive effect on innovation capability through networking capability.